2005
DOI: 10.1007/s11663-005-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of CO-CO2 reaction with CaO-SiO2-FeOx melts

Abstract: Measurements of the rate of interfacial reaction between CO 2 -CO mixtures and CaO-SiO 2 -FeOx slags have been made using the 13 CO 2 -CO isotope exchange technique. Ranges of slag compositions from 0 to 100 wt pct 'FeO' and CaO/SiO 2 between 0.3 and 2.0 were examined in the experiments. For each slag, the dependence of the apparent rate constant on temperature and equilibrium oxygen potential was studied. The relationship between the rate constant and oxygen potential was found to be in the form . The paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 51 publications
5
27
1
Order By: Relevance
“…From the 1960s, the isotope exchange technique, as an effective experimental method to study the interfacial kinetics between gas and iron oxide, has been extensively used by many researchers in metallurgical field. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Recently, in order to meet the strong demand on the utilization of low grade iron ores and reduction of CO2 emission, the direct reduction of fine iron ore, as an innovative ironmaking process, has been given more attention. Therefore, the kinetics of CO2-CO reaction with the solid iron oxide became more important.…”
Section: Introductionmentioning
confidence: 99%
“…From the 1960s, the isotope exchange technique, as an effective experimental method to study the interfacial kinetics between gas and iron oxide, has been extensively used by many researchers in metallurgical field. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Recently, in order to meet the strong demand on the utilization of low grade iron ores and reduction of CO2 emission, the direct reduction of fine iron ore, as an innovative ironmaking process, has been given more attention. Therefore, the kinetics of CO2-CO reaction with the solid iron oxide became more important.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37] Several recent studies [38][39][40][41] have discussed that the reaction of iron oxide in liquid slag with CO-CO 2 gases involves the transfer of charge between the slag and the adsorbed gas species. In order to explore such reaction mechanisms, one needs to gain knowledge of the reaction kinetics and electronic properties of slag under similar conditions.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of papers [11][12][13][14][15][16][17][18][19][20][21][22] devoted to the study on the kinetics of the reduction of FeO and Fe 2 O 3 oxides from slags, but only few deal with the reduction of noneferrous metals from slags. Therefore, an extensive study on the kinetics of copper recovery from industrial slags was undertaken to improve effectiveness of the copper recovery in Głogów smelter.…”
Section: +mentioning
confidence: 99%
“…Barti and Coley [22] investigated the kinetics of the CO-CO 2 reaction with the CaO-SiO 2 -FeO-Fe 2 O 3 slags, with the CaO/SiO 2 ratio varying between 0.3 and 2. They found that the rate constant increases with the iron oxide content, and with the decreasing of the oxygen partial pressure.…”
Section: +mentioning
confidence: 99%